POSTURE ANALYSIS OF MANUAL HANDLING AT PT. X’S WORKSHOP BY REBA METHOD - Abdan Majid; Dian Afif Arifah (Universitas Darussalam Gontor, 2018)
PT. X is one of company engaged in mining contracting, infrastructure, heavy mining equipment providers, and as a place to maintain heavy equipment unit. Workshop Area is a place to do some checking process of unit feasibility and completeness. One of the high risk activity at the workshop of PT. X is manual handling. The repeatedly manual handling will caused muscle disorder and forced worker phisics to extra work. REBA method used to analyze the hazard risk of the activity. This study using observational analytic and involving 6 workers of the different jobs as sample. Results of this study shows that the risk level of manual handling activities in every production is medium, so work position need to be changed to avoid musculoskeletal disorders. Keyword: manual handling; REBA; musculoskeletal disorders